Analisis Pengelolaan Sampah Rumah Tangga melalui Ecobrick di Kelurahan Pekan Labuhan - Rifdah, Annisa Aisy; Susanti, Nofi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Garbage is something that is not used, not used, unpleasant or something that is thrown away that comes from human activities and does not happen by itself. Data shows that the amount of plastic waste in Indonesia is around 7.2 million tons per year (Adharsyah, 2019). Indonesia is in second place after producing 187.2 million tons of waste to the sea after China's 262.9 million tons (Wahyuni, 2016). The purpose of this paper is to analyze household waste management through ecobricks in Pekan Labuhan Village. This study uses qualitative methods in the form of primary and secondary data. The results of this study found that waste, especially household waste, would be more effective and efficient if the management was carried out collectively/communally starting from a small scope (family, village, and village). The conclusion of this study is that the use of ecobricks is, among others, as a material for making furniture, spaces, gardens, and buildings.